2013
DOI: 10.1088/1741-2560/11/1/016002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tDCS volume conduction effects in a highly realistic head model

Abstract: Our results allow us to formulate a guideline for volume conductor modeling in tDCS. We recommend to accurately model the major tissues between the stimulating electrodes and the target areas, while for efficient yet accurate modeling, an exact representation of other tissues is less important. Because for the low-frequency regime in electrophysiology the quasi-static approach is justified, our results should also be valid for at least low-frequency (e.g., below 100 Hz) transcranial alternating current stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
178
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(192 citation statements)
references
References 52 publications
14
178
0
Order By: Relevance
“…By extending FOV with a standard head to capture the anatomy down to the neck we demonstrated that capturing current flows through the entire head significantly improved the modeling results. While most studies argue that the CSF and fluid-filled ventricles should be included in models Wagner et al, 2014;Opitz et al, 2015), others have argued that conventional 1 mm 3 MRI resolution cannot measure CSF space accurately and thus, it can be omitted (Im et al, 2008;Park et al, 2011;Jung et al, 2013). Our results indicate that including CSF into the model is important for correctly predicting the magnitude of achieved electric field in the brain.…”
Section: Guidelines For Modelingmentioning
confidence: 76%
“…By extending FOV with a standard head to capture the anatomy down to the neck we demonstrated that capturing current flows through the entire head significantly improved the modeling results. While most studies argue that the CSF and fluid-filled ventricles should be included in models Wagner et al, 2014;Opitz et al, 2015), others have argued that conventional 1 mm 3 MRI resolution cannot measure CSF space accurately and thus, it can be omitted (Im et al, 2008;Park et al, 2011;Jung et al, 2013). Our results indicate that including CSF into the model is important for correctly predicting the magnitude of achieved electric field in the brain.…”
Section: Guidelines For Modelingmentioning
confidence: 76%
“…Two recent simulation studies have extended simple three-compartment head models to complex six-compartment models step-by-step to study the effects of modeling various aspects of the human head [8,27]. Both studies also included anisotropic conductivity information derived from diffusion tensors.…”
Section: Discussionmentioning
confidence: 99%
“…following transcranial direct current stimulation) along trajectories parallel to the primary direction of the fiber tracts [4,27]. Sources located deep in the brain, as well as those bordering strongly anisotropic tissue, are misrepresented in EEG localization when neglecting the effects of white matter anisotropy [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations